AFLPmatrix_original_B_nana - Eidesen, Pernille Bronken; Alsos, Inger Greve; Brochmann, Christian (Dryad Digital Repository, 2015)
Binary AFLP matrix with 119 markers, 570 individuals of Betula nana and B. glandulosa generated by 3 primer combinations